The relationship between sexuality and temperament in patients with epilepsy - V. G. Sosnina; D. M. Saraykin; L. V. Lipatova (Эпилепсия и пароксизмальные состояния)
Aim: to study the relationship between sexuality and temperament in patients with epilepsy.Materials and methods. The study included 102 participants: 52 patients with epilepsy and 50 healthy individuals aged from 19 to 45 years. The psychological examination was based on the I-structural test of Ammon (ISTA), the Structure of temperament questionnaire (STQ) of Rusalov, and a clinical interview.Results. Using the correlation analysis we were able to reveal 9 correlations between the types of sexuality and the temperament characteristics in patients with epilepsy; in subjects of the control group – 4 correlations were found. Thus, in patients with epilepsy, constructive sexuality positively correlated with plasticity, social erginess, and pace, whereas in healthy subjects – with social erginess. In patients with epilepsy, destructive sexuality positively correlated with plasticity, social erginess, and social plasticity; in healthy subjects, destructive sexuality negatively correlated with social erginess. In patients with epilepsy, deficient sexuality negatively correlated with pace, plasticity, and social erginess, whereas in healthy subjects – with plasticity and social plasticity.Conclusion. The study shows that the sexuality in patients with epilepsy is more deterministic than that in the comparison group. In addition, all types of sexuality in these patients correlate with plasticity and social erginess, which suggests that patients with epilepsy can be satisfied with sexual relations, show flexibility and strive for diversity while being flexible and socially active. These correlations can be read vice versa, i.e., striving for diversity and social activity in patients with epilepsy is accompanied by satisfaction with their sexual relations and inclination to experiment.